Persepsi Stres Kerja dari Kacamata Perempuan - Kusprihandini Kusprihandini; Abu Talkah; Arisyahidin Arisyahidin (Universitas Islam Kadiri, 2022)
COVID-19 is a nightmare for everyone. How can this pandemic still continue to spread and it is not known with certainty the end of COVID-19. Various sectors, both business and office sectors, are feeling the impact of the spread of the COVID-19 pandemic, including in Indonesia. Government regulations related to the rules for implementing work from home are pros and cons in various parties, for example in Sanankulon District, Blitar Regency where the area is not too wide but is still required to be able to manage human resources in it well. Evidence of the success of human resource management is by observing whether or not there is an increase in work stress in the Sanankulon District, Blitar Regency, especially for village officials who are married and are female, of course this needs special attention. In fact, women who have multiple roles are more at risk of experiencing work stress. For this reason, this research was conducted to observe what has an impact on work stress. This study uses a quantitative descriptive approach with the completion of multiple linear regression analysis. This study resulted in the finding of a positive influence between the independent variables on the dependent variable.